Writing exile: Fulvio Tomizza - Deganutti, M (2014)
This thesis focuses on the unusual phenomenon of exile from a frontier land, as it is explored by the work of the Istrian writer Fulvio Tomizza. It deals with the diaspora from Istria, a territory at the intersection of different civilizations – the Italian and the Croat-Slovenian – which has historically shaped a mixture of cultures and languages, remarkable for its hybridity. The massive exile which took place at the end of the Second World War, after the redefinition of the Italo-Yugoslav border, presents original features which, by taking advantage of the narrative tool, overturn traditional parameters attributed to exile. Focusing on Fulvio Tomizza’s novels Materada, La ragazza di Petrovia and L’albero dei sogni, and also on some of his most significant essays, I will seek to outline the specific traits that typify the detachment from one’s own native country. In particular, I shall suggest that identity and idioms are called into question even before characters have left their homeland. In addition, exile begins with a clarification of characters’ sense of belonging, which inevitably leads them to split, making the choice of whether to abandon the home country even more complicated. Once abroad, characters will develop a deep sense of estrangement, dictated by the impossibility of fitting into any other context, which will eventually drive them to a double, parallel, unsuccessful exile. In order to investigate fully the characteristics of Fulvio Tomizza’s exile, I will employ some linguistic postulates to examine the bilingualism and diglossia of the origins. The theoretical approaches of Edward Said, Sigmund Freud and Julia Kristeva will be used to inform my analysis of the more subtle mechanisms which rule exile, starting with doubleness and examining the dynamics which commonly characterize the exilic experience, including those in relation to the elaboration of the narrative itself. The novelty of this work lies in its approach to exile without preconceived arguments, which run the risk of limiting the analysis of the topic, and in the exploration of the most crucial aspects of a frontier land shaken by a territorial redefinition. This thesis also aims to reallocate the figure of Fulvio Tomizza, who has as yet not been investigated in any significant manner, most often being neglected or misunderstood. The aim is also to highlight one of the most European writers of the Italian second Novecento and his relationship with Eastern European languages and literatures.